Inovasi dalam Pembelajaran PPKN Menggunakan Media Tradisional dan Digital di Madrasah Ibtidaiyah - salsabila, Bilqis Salsabila Mayada; Salsabila, Lailia; Nasir, M.Fikri Abdun (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
The development of information and communication technology has brought significant changes to the world of education, including in Citizenship Education (PKN) learning. This research aims to explore PKN learning innovations in the digital era with technology to improve student understanding. The research method used is a comprehensive literature study from various related sources, such as journals, books and research reports. The research results show that the use of technology in PKN learning, such as interactive multimedia, digital simulations, and online learning, can increase students' interest, motivation, and understanding of PKN material. Apart from that, the use of technology also enables more contextual, collaborative and student-centered learning. However, the application of technology in PKN learning also has challenges, such as limited access to technology and teacher readiness to integrate technology effectively. This research concludes that PKN learning innovation in the digital era using technology can be a solution in improving the quality of education and preparing students to become active, critical and responsible citizens in the digital era.